2015
DOI: 10.3171/2014.10.jns141246
|View full text |Cite
|
Sign up to set email alerts
|

Vascular consequences of operculoinsular corticectomy for refractory epilepsy

Abstract: OBJECT Surgery in the insular region is considered challenging because of its vascular relationships, the proximity of functional structures, and its deep location in the sylvian fissure. The authors report the incidence and consequences of ischemic lesions after operculoinsular corticectomy for refractory epilepsy. METHODS The authors retrospectively reviewed the data of all patients who underwent an insular resection with or without an opercular resection for refractory epilepsy at their center. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
(33 reference statements)
3
18
1
Order By: Relevance
“…7,36,37 Furthermore, series showed that favorable seizure outcome was obtained in the majority of the patients, with functional risks considered acceptable, despite ischemic lesions being observed in 60% of the cases. 19 The largest series (25 patients) reported that paresis, dysphasia, alteration of taste, smell, hearing, pain, and thermal perceptions were frequent (75%), but always transient except for one patient with persistent mild alteration of thermal and pain perception. 20 In addition, no major cognitive deterioration was reported by this group.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…7,36,37 Furthermore, series showed that favorable seizure outcome was obtained in the majority of the patients, with functional risks considered acceptable, despite ischemic lesions being observed in 60% of the cases. 19 The largest series (25 patients) reported that paresis, dysphasia, alteration of taste, smell, hearing, pain, and thermal perceptions were frequent (75%), but always transient except for one patient with persistent mild alteration of thermal and pain perception. 20 In addition, no major cognitive deterioration was reported by this group.…”
Section: Discussionmentioning
confidence: 97%
“…However, the initial reports included mainly lesionectomies or were limited to few patients and most often in nondominant hemispheres, including pediatric cases . Furthermore, series showed that favorable seizure outcome was obtained in the majority of the patients, with functional risks considered acceptable, despite ischemic lesions being observed in 60% of the cases . The largest series (25 patients) reported that paresis, dysphasia, alteration of taste, smell, hearing, pain, and thermal perceptions were frequent (75%), but always transient except for one patient with persistent mild alteration of thermal and pain perception .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations